2010
DOI: 10.1094/cchem-87-3-0182
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Susceptibility at Four Temperature‐Moisture Combinations and Carbon Dioxide Kit Color Reader Evaluation

Abstract: The susceptibility of shelled corn to invasion by storage fungi was assessed using a carbon dioxide (CO2) test kit. Shelled corn samples were rewetted to either 16 or 21% wb moisture content (MC) and incubated ≤80 hr at either 24 or 30°C in sealed glass jars. CO2 concentration in the jars was quantified using the color number (0–5) of an indicator gel, which was determined either by visual comparison to a color card (VR) or using a Digital Color Reader (DCR). Plots of DCR color numbers versus time were smoothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Huang et al (2013) and Chidananda et al (2014) reported that respiration rate increased when temperature and grain moisture content increased. Moog et al (2010) reported that the temperature had a greater effect than moisture content on fungal susceptibility measurements during the storage of shelled corn samples. G omez et al (2014) mentioned that the high temperatures accelerate chemical reactions and respiration rates as well as they expedite the occurrence of the climacteric peak.…”
Section: Effects Of Corn Moisture Content Storage Temperature and Smentioning
confidence: 99%
“…Huang et al (2013) and Chidananda et al (2014) reported that respiration rate increased when temperature and grain moisture content increased. Moog et al (2010) reported that the temperature had a greater effect than moisture content on fungal susceptibility measurements during the storage of shelled corn samples. G omez et al (2014) mentioned that the high temperatures accelerate chemical reactions and respiration rates as well as they expedite the occurrence of the climacteric peak.…”
Section: Effects Of Corn Moisture Content Storage Temperature and Smentioning
confidence: 99%
“…Lacey et al (1994) concentrations increased with the increase in storage duration, grain moisture content, and temperature. Moog et al (2010) reported a similar effect where the temperature had a higher effect than grain moisture content on fungal susceptibility measuring during the storage of shelled corn cereals. Huang et al (2013) Lacey et al (1994) cited that respiration increased linearly with temperature up to 35 °C and that it also increased with time and seed moisture content in barley, wheat, rapeseed, and linseed.…”
Section: Discussionmentioning
confidence: 75%